Da’wa Strategy of the Nurcu Movement as a Counterhegemony to the Secularism in Turkey - Nurhalizah, Mevy Eka; Musthafa, Chabib (International Journal of Islamicate Social Studies, 2023)
This research seeks to answer how the Nurcu movement's proselytizing strategy as a counterhegemony of secularism in Turkey with the perspective of hegemony theory and authority conflict theory. Research questions were answered by using literature studies, with a close historical and sociological analysis of the preaching strategy undertaken by the Nurcu movement in Turkey through research by other relevant sources. The study results show that the Nurcu Movement’s proselytizing strategy is an effective proselytizing strategy to counter Attaturk’s secular hegemony in Turkey. This is because the Nurcu movement implemented a "position war" and a "maneuver war" to carry out resistance to secularism in Turkey. In addition, Nursi and his followers can change the situation with the necessary understanding of religion and are able to turn conflict into consensus. The Nurcu movement preached culturally and persuasively with the civilizational dialogue method. In addition, this movement utilizes the fields of education, journalists, media and economics to utilize its da'wa